A Civilian Ownership and Use of Firearms in Indonesia: A Juridical and Human Rights Analysis - Yoga Wiratama; Gunawan Djajaputra (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This study explores the legal mechanisms that govern civilian firearm ownership and utilization within Indonesia, examined from both juridical and human rights perspectives. The primary aim of this investigation is to analyze the statutory framework controlling civilian gun possession, evaluate the implementation of existing regulations, and identify challenges in firearm surveillance and regulation. The research adopts a normative legal methodology incorporating statutory analysis and comparative examination approaches. Results indicate that Indonesia implements highly restrictive measures regarding civilian firearm ownership through an extensive licensing framework, as outlined in National Police Regulation Number 1 of 2022. The investigation also identified significant gaps between comprehensive regulatory provisions and practical enforcement, especially concerning the oversight of unauthorized weapon distribution. The study concludes that enhanced inter-agency monitoring systems and collaborative frameworks are essential to achieve balance between personal security entitlements and collective public protection.